Atomic bond proportions and relations to physical properties in metallic glasses. (January 2015) - Zhao, W.; Li, G.; Wang, Y.Y.; Feng, S.D.; Qi, L.; Ma, M.Z.; Liu, R.P.
Highlights: A new structural parameter, atomic bond proportion, was proposed. Two calculation methods of atomic bond proportion were successfully given. Weighted averages of the atomic bonds can be used to estimate physical properties. Abstract: Identifying the underlying mechanisms of the special physical properties of metallic glasses (MGs) is of fundamental interest. The complexity and uncertainty in the structure of MGs have been obstacles to develop an efficient structure–property relationship. In this letter, we present a simplified structural parameter, atomic bond proportion, instead of exploring the complicated atomic structure to predict the properties of MGs. Based on statistical calculations and partial coordination number methods, the proportion of different types of atomic bonds for a series of MGs (e.g., Ca60 Mg15 Zn25, Zr67 Ni33, and Al90 Y10 ) is successfully given, and the results from both methods significantly agree with each other. The weighted averages of the physical properties corresponding to the constituent atomic bonds were used to analyze the relationship between the composition and physical properties. The predicted atomic bond proportion may better elucidate the structure and properties of these materials.